2013
DOI: 10.1111/cts.12066
|View full text |Cite
|
Sign up to set email alerts
|

Provider's Perspectives on Building Research and Quality Improvement Capacity in Primary Care: A Strategy to Improve Workforce Satisfaction

Abstract: Objectives: Safety-net populations are underrepresented in research and quality improvement (QI) studies despite the fact that safetynet providers are uniquely positioned to engage in translational research. This study aimed to understand the current level of interest in, experience with, predicted career satisfaction associated with, and barriers experienced in conducting research and QI among primary care providers (PCPs) at 18 safety-net practices in the Boston, Massachusetts area. Methods: The Harvard Cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…Government investment in supporting academics and supporting establishing PBRNs are necessary in order to build research capacity in primary care [53]. Levers for overcoming the barriers of time and skills capacity, include buying GPs out of clinical time to engage in research and to partner with academics for research training [54].…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…Government investment in supporting academics and supporting establishing PBRNs are necessary in order to build research capacity in primary care [53]. Levers for overcoming the barriers of time and skills capacity, include buying GPs out of clinical time to engage in research and to partner with academics for research training [54].…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…When retention is jeopardized among individual providers, it risks the larger CHC workforce. Independent studies [12][13][14] all confirm the need to bring together mission-driven providers with opportunities that address the non-patient care interests of this workforce (i.e., opportunities for research, teaching, and QI as well as work/ life balance, part-time status, and professional development). Mission may bring providers to CHCs, but without addressing retention, many physicians, especially new graduates, may choose to move to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al found that part-time status, access to wellness programs, and practicing in non-rural locations were significant factors for providers remaining at their current location as were practicing for longer than five years in an underserved location 12 and pursuing quality improvement (QI) and research opportunities. 13,14 Hayashi also found that workplace stress, exacerbated by a full-time schedule or isolated geographic location, reduced the likelihood of working in a CHC for significant lengths of time. While Title VII funding for training primary care physicians has been successful in increasing provider supply, many of these new clinicians are ultimately choosing nonprimary care careers.…”
mentioning
confidence: 98%
“…Healthcare professionals working within AHSCs are well positioned to carry out collaborative practice-based research due to their proximity to patients and opportunity to generate clinically driven research questions; [5,7] particularly nurses and health disciplines that collectively comprise the largest healthcare workforce within health care. [5] There are reported benefits around engaging nurses and health disciplines in research in healthcare organizations including increased research productivity, efficiency and reduced patient mortality and morbidity; [8,9] uptake of evidence; [9,10] increased job satisfaction [11] and reduced staff turnover. [8,9] However, although there is a body of literature around discipline specific capacity building research, [4,10,12] there is less known empirically around collaborative practice-based research; particularly in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…[5] There are reported benefits around engaging nurses and health disciplines in research in healthcare organizations including increased research productivity, efficiency and reduced patient mortality and morbidity; [8,9] uptake of evidence; [9,10] increased job satisfaction [11] and reduced staff turnover. [8,9] However, although there is a body of literature around discipline specific capacity building research, [4,10,12] there is less known empirically around collaborative practice-based research; particularly in Canada. Research involvement from nurses; [13,14] and health disciplines [4,7,15] continues to remain low.…”
Section: Introductionmentioning
confidence: 99%